Growth, interfacial microstructure and optical properties of NiO thin films with various types of texture. (1st February 2019) - Wang, Y.; Ghanbaja, J.; Boulet, P.; Horwat, D.; Pierson, J.F.
Abstract: NiO thin films with random, fiber and in-plane textures have been successfully deposited at near room temperature by reactive magnetron sputtering on glass, silicon and Al2 O3 (0001) substrates. Self-texture related with the deposition conditions and crystallographic characters competes with the driving force from the matched substrate. Such a competition can be used to control the texture of thin films on matched substrates, especially when the promoting orientations from self-texture and substrate are different. Enhancing this competition tends to suppress the self-texture of NiO thin films on Al2 O3 (0001) substrates, whereas restricting the competition is beneficial to produce the in-plane textured NiO thin films. In addition, it is found that the optical transmittance of NiO thin films on Al2 O3 (0001) substrates can also be tuned by such competition. Interfacial microstructure analyses of NiO thin films on amorphous substrates clearly evidence the existence a nanocomposite layer at the initial growth, which is composed of NiO nanocrystals surrounded by amorphous matrix. In contrast, in-plane textured NiO thin films on Al2 O3 (0001) substrates exhibit sharp interface without nanocrystals or amorphous matrix. We believe these results provide a general framework of tuning the textures and properties of thin films on matched substrates. Graphical abstract: Image 1